The Influence of Marketing Communication Factors towards Decision Making of Private Hospital Customer in Mueng District Phuket Province - ปะณะรักษ์ ณิชชา (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The research purposes were to; 1) study the influence of marketing communication factors towards decision making of private hospital customer in Mueng district Phuket province and, 2) compare the personal factors with the marketing communication level to influence in the service user decision of the private hospital in Muang district Phuket province. The samples were 400 of customers in Phuket private hospital. A questionnaire was used to collect data. Descriptive statistics; frequency, percentage, mean, standard deviation and inferential statistics; t-test, and One-Way ANOVA, were used in the data analysis. The research results found that; The influence of marketing communication tools towards decision making of private hospital customer in Mueng district Phuket province. In the overall, the customers decision of the Phuket private hospital was at a high level. In descending order of the average, there were the marketing activities, advertising, public relations, sales by salesman, marketing support, promotion, direct communication and point of purchase communication. The comparison between the marketing communication tools towards decision making of private hospital customer in Mueng district Phuket province by distinguishing of the personal factors found that the factors in gender, age, education, occupation, marital status, average income per month and frequency in using the service were different at statistical significance at the .01 level.